2016
DOI: 10.4103/1735-9066.185610
|View full text |Cite
|
Sign up to set email alerts
|

The effect of teacher′s presence at children′s bedside on the anxiety of mothers with hospitalized children: A randomized clinical trial

Abstract: Background:The hospitalization of a child is a stressful experience for parents, especially mothers. Not having access to the teacher and not being able to continue school studies within the hospital by hospitalized children is a common reason for anxiety in them and their parents. The current study aimed to determine the effect of teacher's presence at children's bedside on the anxiety of mothers with hospitalized children.Materials and Methods:In a randomized clinical trial, a total of 50 mothers with childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
4
0
2
Order By: Relevance
“…In the hospital context, the ability to prepare a sound teaching program is seen to be secondary to the creation of solid, trust-based relationships with students and their families ( Benigno et al, 2017 ). As such, Reyhani, Aemmi, & Zeydl ( 2016 ) reported that the presence of a teacher at the child’s bedside is a simple and effective strategy to reduce mothers’ anxiety regarding their child’s hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…In the hospital context, the ability to prepare a sound teaching program is seen to be secondary to the creation of solid, trust-based relationships with students and their families ( Benigno et al, 2017 ). As such, Reyhani, Aemmi, & Zeydl ( 2016 ) reported that the presence of a teacher at the child’s bedside is a simple and effective strategy to reduce mothers’ anxiety regarding their child’s hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Reyhani ve ark. 'larının 6-12 yaş arası çocuk ve ebeveynleriyle yaptığı bir çalışmada, çocuklarına eğitim desteği verilen ebeveynlerin anksiyete düzeyi, çocuklarına eğitim desteği verilmeyen ebeveynlerin anksiyete düzeyinden çok daha düşük bulunmuştur (28).…”
Section: Discussionunclassified
“…Music is one of the proven non‐pharmacological tools and nursing interventions that have been widely used for centuries in various cultures to reduce negative emotions such as pain, anxiety and depression, and to increase patient comfort (Witusik & Pietras, 2019). In recent years, music emerged as a frequently preferred method to control the adverse effects of the intensive care environment and the general condition of the patients and is accepted as an easy‐to‐use, non‐invasive and side‐effect‐free tool (Jafari et al, 2012). In the literature, music‐based applications are presented in various names in healthcare settings.…”
Section: Introductionmentioning
confidence: 99%